Hydroxychloroquine availability during COVID-19 crisis and its effect on patient anxiety - Alain Cornet; Chiara Tani; Marta Mosca; Jeanette Andersen (Lupus Science and Medicine)
Objective To report the results of a survey exploring the experience of patients with SLE facing hydroxychloroquine (HCQ) shortage that occurred during the early phases of the COVID-19 pandemic.Methods A survey was designed by Lupus Europe’s patient advisory network and distributed through its social media, newsflash and members' network. People with lupus were asked about their last HCQ purchases and their level of anxiety (on a 0–10 scale) with regard to not being able to have access to HCQ, once in April 2020 (first wave) and after 11 August (second wave). The results were compared.Results 2075 patients responded during the first wave; 1001 (48.2%) could get HCQ from the first place they asked, 230 (11.1%) could get the drug by going to more than one pharmacy, 498 (24.0%) obtained HCQ later from their usual pharmacy and 126 (6.1%) from other sources. 188 (9.1%) could not get any; 32 (1.5%) did not respond to this question. All countries showed significant improvement in HCQ availability during the second wave. 562 (27.4%) patients reported an extremely high level of anxiety in wave 1 and 162 (10.3%) patients in wave 2; 589 (28.7%) and 268 (17.1%) patients reported a high level of anxiety in wave 1 and wave 2, respectively.Conclusions The HCQ shortage had a significant impact on patients with SLE and has been responsible for psychological consequences including anxiety. Indeed, despite an objective improvement in drug availability, the event is leaving significant traces in patients’ mind and behaviours.